1,3-Bis(5,6,7,8-tetrahydrobenzo[4,5]thieno[2,3-d]pyrimidin-4-yl)imidazolidine-4,5-dione - Xuelian Yin; Sung Min Kim; Yang-Heon Song (Molbank, 2022)
A thieno[2,3-d]pyrimidine derivative 3 bearing a 4,5-imidazolidinedione moiety, 1,3-bis(5,6,7,8-tetrahydrobenzo[4,5]thieno[2,3-d]pyrimidin-4-yl)imidazolidine-4,5-dione, was efficiently synthesized in 66% yield by the reaction of N,N′-bis(5,6,7,8-tetrahydrobenzo[4,5]thieno[2,3-d]pyrimidin-4-yl)methanediamine 2 with oxalyl chloride in the presence of pyridine in refluxing dichloroethane for 10 h. The structure of the new synthesized compounds was fully characterized by 1H, 13C NMR, IR spectroscopy, mass-spectrometry and elemental analysis.